2019
DOI: 10.3389/fchem.2019.00172
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Peptides as Extracellular Matrix Mimics to Influence Stem Cell's Fate

Abstract: Interest in biologically active materials that can be used as cell culture substrates for medicinal applications has increased dramatically over the last decade. The design and development of biomaterials mimicking the natural environment of different cell types, the so-called extracellular matrix (ECM), is the focus of research in this field. The ECM exists as an ensemble of several adhesion proteins with different functionalities that can be presented to the embedded cells. These functionalities regulate num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 85 publications
0
48
0
Order By: Relevance
“…The materials synthesized as the mimetics of the natural ECM that were analyzed in this study differ from most of the hydrogels reported in the literature [37] and/or those available commercially. While the peptide fragments of collagen have been used as substrates for cell cultures [38,39], in our PEG-peptide hydrogels, the native-like assemblies of the peptides are facilitated by the covalent attachment to an eight-armed PEG-maleimide. The overall architecture is further locked by chemical crosslinking, as described in [22].…”
Section: Discussionmentioning
confidence: 99%
“…The materials synthesized as the mimetics of the natural ECM that were analyzed in this study differ from most of the hydrogels reported in the literature [37] and/or those available commercially. While the peptide fragments of collagen have been used as substrates for cell cultures [38,39], in our PEG-peptide hydrogels, the native-like assemblies of the peptides are facilitated by the covalent attachment to an eight-armed PEG-maleimide. The overall architecture is further locked by chemical crosslinking, as described in [22].…”
Section: Discussionmentioning
confidence: 99%
“…Materials cytotoxicity assessment results, following the ISO 10993-5:2009, showed no significant differences in percentage of cell viability at all timepoints, indicating that neither the PCL scaffolds nor the RAD16-I peptide are toxic for cells and that chloroform was successfully removed from PCL scaffolds. Interestingly, only cells cultured in RAD peptide conditioned medium at 72 h exhibited significant higher levels of cell viability (%), confirming the proliferation-enhancing potential of RAD16-I self-assembling peptide [47].…”
Section: Discussionmentioning
confidence: 58%
“…Those peptides are advantageous owing to their easy and cost‐effective synthesis, biocompatibility, biodegradability, self‐assembling capability into fibrillar nanostructures in aqueous media, and customized bioactivity, which turns them into suitable molecular building blocks for engineering artificial ECM‐mimetic constructs to direct cell fate . Such peptide library would encompass the widely studied FN‐derived RGD and laminin‐derived IKVAV (isoleucine‐lysine‐valine‐alanine‐valine) biofunctional peptide sequences, known to modulate cellular functions at the tissue and organ levels, among many others, opening new avenues in the molecular design of innovative ECM‐like biomaterials for addressing a number of different tissue engineering applications . When envisioning the assembly of dense LbL‐built microtissues important aspects regarding nutrients/oxygen availability and neo‐vascularization must be considered to assure cellular viability and biofunctionality in denser microtissue constructs.…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%